Produksi Film Animasi 2D Pool - Meidiana Safitri; Tanto Harthoko; Andri Nur Patrio (Institut Seni Indonesia Yogyakarta, 2020)
The story of a boy named Boy who is trying to overcome his trauma to a swimming pool. Trauma is the result of a terrible experience that has occurred during life. With a long recovery time, a trauma sufferer always imagines bad events and some traumatic symptoms that is difficult to overcome. Therefore, the character needs the support of the closest people to recover slowly. The creation of 2D animated film